2009
DOI: 10.1016/j.actbio.2008.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Neomycin binding preserves extracellular matrix in bioprosthetic heart valves during in vitro cyclic fatigue and storage

Abstract: Bioprosthetic heart valve (BHV) cusps have a complex architecture consisting of an anisotropic arrangement of collagen, glycosaminoglycans (GAGs) and elastin. Glutaraldehyde (GLUT) is used as a fixative for all clinical BHV implants; however, it only stabilizes the collagen component of the tissue, and other components such as GAGs and elastin are lost from the tissue during processing, storage or after implantation. We have shown previously that the effectiveness of the chemical crosslinking can be increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…Incorporation of PGG into neomycin and GLUT cross-linking demonstrated that PGG binding improved GAG stabilization achieved by neomycin alone, published elsewhere. 12 This demonstrates that the combination of neomycin and PGG not only maintains GAG stabilization potential of neomycin in porcine aortic leaflets but also improves it probably due to synergistic effects of reactions with additional functional groups. Neomycin is a hyaluronidase inhibitor with multiple amine functionalities, 15,31 while PGG has multiple phenolic hydroxyl groups.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Incorporation of PGG into neomycin and GLUT cross-linking demonstrated that PGG binding improved GAG stabilization achieved by neomycin alone, published elsewhere. 12 This demonstrates that the combination of neomycin and PGG not only maintains GAG stabilization potential of neomycin in porcine aortic leaflets but also improves it probably due to synergistic effects of reactions with additional functional groups. Neomycin is a hyaluronidase inhibitor with multiple amine functionalities, 15,31 while PGG has multiple phenolic hydroxyl groups.…”
Section: Discussionmentioning
confidence: 78%
“…30 Therefore, an in vitro combination of chondroitinase and hyaluronidase was used to evaluate the resistance to enzymatic GAG loss. We have shown earlier that the addition of neomycin enhances GAG stabilization in BHVs, 12 but how PGG addition will affect neomycin-based GAG stabilization was not previously investigated. Incorporation of PGG into neomycin and GLUT cross-linking demonstrated that PGG binding improved GAG stabilization achieved by neomycin alone, published elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…20 and Raghavan et al . 54 also observed leaflet microstructural changes including damage to the type I collagen 20 and loss of GAG content. 20,54 These studies have been particularly useful in identifying concentrated damage regions within the leaflets and flawed designs.…”
Section: Experimental Characterization Of Fatigue Damage In Soft mentioning
confidence: 85%
“…Raghavan et al . 54 determined that glutaraldehyde only stabilizes the collagen component of the porcine BHV leaflets, and thus GAGs leach out under conditions of fatigue. 20 For this reason, the long-term fatigue response of glutaraldehyde-treated tissues is primarily based on the collagen fibers.…”
Section: Experimental Characterization Of Fatigue Damage In Soft mentioning
confidence: 99%
See 1 more Smart Citation